THE RECOVERY OF THE ESTHETIC AND MASTICATORY FUNCTIONS BY MINIMAL INVAZIVE RESTORATIONS - Andrei Kozma; Cristina Bodnar; Mădălina Dobre; Doriana Agop-Forna; Claudiu Topoliceanu; Horia Lăzărescu; Norina Forna (Romanian Society of Oral Rehabilitation, 2019)
Abstract. As dental caries is a common disease with high prevalence worldwide, many researches are focused nowadays on the longevity of direct composite restorations and indirect restorations both in the anterior and posterior dental substance loss. The mean survival rates of the direct composite restorations, after follow-up period of 3-10 years, are between 85,10% and 97,40%. The mean survival rates of the indirect coronal restorations, after follow-up period of 8-10 years, are between 90,40% and 100%. In the recovery of the esthetic and masticatory functions affected by coronal substance loss, the direct composite restorations and ceramic inlays or onlays have advantages and limits. The dentists must focus on factors related to material and technique as well as on clinical and biological factors, when a repair versus replacement decision must be taken